Comparative study on process-structure-property relationships of TiC/Ti6Al4V and Ti6Al4V by selective laser melting. (1st March 2023) - Jiang, Qinghong; Li, Shuai; Guo, Sai; Fu, Mingwang; Zhang, Bi
Highlights: Near fully dense titanium alloy and TMCs samples are fabricated by SLM. Ultrafine microstructures are obtained in SLM-ed titanium alloy and TMCs. Strong and ductile Ti6Al4V and ultra–strong TiC/Ti6Al4V specimens are fabricated. An evolution process is proposed to describe the microstructure formation of SLM-ed TMCs. SLM-ed titanium alloy and TMCs exhibit completely different fracture mechanism. Abstract: Titanium matrix composites (TMCs) have gained tremendous attention due to their excellent mechanical properties by combining the advantages of Ti6Al4V matrix and ceramic reinforcement. In current study, the selective laser melting (SLM) technique is applied to manufacture TiC/Ti6Al4V and Ti6Al4V. Systematic characterization and analysis are conducted to reveal and compare their process-structure-property relationships. The results reveal that the near fully dense parts could be manufactured by process optimization upon the systematic investigation on their densification behaviors. The addition of TiC effectively refines the matrix grain and changes the microstructures. The SLM-manufactured (SLM-ed) Ti6Al4V exhibits typical coarse columnar grains with ultrafine lamellar α+β microstructures distributed inside (average α-lath thickness: 282 nm). Nevertheless, the SLM-ed TMCs possess a peculiar molten pool morphology, in which the sub-columnar grains grow upward along the direction of the steepest temperature gradient. The acicular nanoscale TiC is dispersed inside the sub-columnar grains, while the chain-like TiC is distributed along the boundary. Meanwhile, an evolution process is proposed to describe the microstructure evolution of the SLM-ed TMCs. The interrelationships between energy density and resulting microstructures are also identified, based on which, strong and ductile Ti6Al4V specimens (tensile strength: 1390 MPa, elongation: 9.66%) and ultra-strong TMCs specimens (tensile strength: 1538 MPa) are manufactured. The strengthening effects are mainly attributed to the Hall-Petch strengthening and load-bearing transformation. Fracture analysis indicates that the failure of the SLM-ed Ti6Al4V is caused by the micro-voids nucleation and coalescence at the interface of α and β phases, whereas the premature fracture of the SLM-ed TMCs is originated from the chain-like TiC. Graphical abstract: Image, graphical abstract